Intra-varietal variability of Romanesco variety (Vitis vinifera L.) - Muganu Massimo; Paolocci Marco; Primiceri Simona; Tartaglia Riccardo; Benucci Ilaria; Cerreti Martina; D'Onofrio Claudio; Paolacci Anna Rita; Bignami Cristina (BIO Web of Conferences, 2019)
Most historical sources that describe the presence of Romanesco variety in vine-growing areas of Lazio Region (Italy) highlighted the variability of morphological traits within the variety. This partly justifies the presence of different synonyms, true or presumed, reported by many authors for this grape variety. With the aim of analysing this variability, eight accessions related to the variety, collected in Lazio Region and grown in the DAFNE grape germplasm collection, have been characterized over five productive seasons. The ampelographic description was carried out using 50 OIV morphological descriptors and ampelometric analyses were carried out on mature leaves by SuperAmpelo software. The DNA of the different accessions, extracted from young leaves, was analyzed using 14 microsatellite loci. Furthermore, at harvest, the grapes of each accession were sampled to assess main compositive characteristics. Results showed differences among accessions on some ampelographic descriptors of the mature leaf, of the bunch, and on phenological stages. Microsatellite profiles allowed for classification of the accessions into three distinct groups. Qualitative analysis of the berry skin showed differences among accessions in the content of the main classes of phenolic compounds.